Implementation of the JKN Tiered Referral System: A PRISMA-Based Systematic Literature Review and Bibliometric Analysis of Healthcare Management Challenges - Kosasih Kosasih; Alif Yosi Samrotul Qolbi; Annisa Dwi Ramdania Pamungkas; Muthia Isratnasari; Leoni Ester Manukiley (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the implementation of the tiered referral system under Indonesia’s Jaminan Kesehatan Nasional (JKN) program and analyzes the dilemma between service quality and cost control from healthcare management and public policy perspectives. Research Method: This study employed a Systematic Literature Review (SLR) using the PRISMA framework, complemented by bibliometric analysis with VOSviewer. Data were drawn from national and international scientific publications published between 2020 and 2025 concerning tiered referrals, healthcare service quality, and cost efficiency under JKN. Results and Discussion: The findings show that multidimensional challenges, including limited healthcare resources, inadequate infrastructure, low patient compliance, and weak coordination across healthcare levels, hinder implementation. Bibliometric mapping indicates growing research interest and a thematic shift from service quality and cost efficiency toward patient behavior, healthcare accessibility, digital health transformation, and integrated care. The analysis confirms a persistent trade-off between improving service quality and controlling healthcare expenditure, driven by structural and managerial constraints. Implications: The study highlights the need for integrated management strategies that balance quality improvement and cost containment. Strengthening primary care, referral coordination, patient compliance, and digital health adoption is essential for JKN sustainability. Originality: This study integrates PRISMA-based SLR and bibliometric analysis to provide a comprehensive assessment of Indonesia’s JKN tiered referral system.